The Effectiveness of Ginging Candy Against Nausea and Vomiting in Pregnant Mothers at The Joint Maternity Clinic North Padang Lawas District - Riska Yanti Harahap (International Journal of Public Health Excellence (IJPHE), 2022)
Pregnancy causes many changes in the mother's body, there will be various kinds of physiological discomfort in the mother, such as nausea and vomiting, usually mild and a condition that can be controlled according to the mother's condition. This condition sometimes stops in the first trimester, but its effects can cause nutritional disorders, dehydration, weakness, weight loss, and electrolyte imbalance , if not treated it will increase in weight to Hyperemesis Gravidarum . This study aims to determine the effectiveness of ginger candy in reducing the frequency of nausea and vomiting in first trimester pregnant women at the Joint Maternity Clinic with a Quasy Experimental study design with a One Group Pretest Posttest design. Respondents used were 15 people with purposive sampling technique . This data was taken using the T - dependent test . The results showed that the frequency of nausea and vomiting before the intervention was given was 10.93 and after the intervention was 3.33 with an average decrease of 7.60. The results of statistical tests obtained p value < (0.05) so it can be concluded that the administration of ginger candy is effective in reducing nausea and vomiting in first trimester pregnant women.